Why do women attend late for antenatal booking? A qualitative interview study exploring the perspectives of service users and stakeholders. (13th September 2011) - Jones, GL; Haddrill, R; Mitchell, C; Anumba, DA
Abstract : Introduction: Delayed access to antenatal care ('late booking') has been linked to increased mortality and morbidity for mother and baby. The Confidential Enquiry into Maternal Deaths in the UK (2007) found that 17% of the women who died from Direct or Indirect causes booked for maternity care after 22 weeks gestation, had missed >4 routine antenatal visits or didn't seek care at all. Little explanatory qualitative research has been undertaken outside the USA. This study explored the reasons why women book late from (1) the perspectives of pregnant women who booked after 19 weeks gestation and (2) key maternity stakeholders involved in the care of antenatal women. Method: Purposive sample of women booking >19 weeks gestation, from hospital, community and specialist antenatal clinics. Face-to-face, individual interviews in women's homes, hospital clinics and children's centres. Purposive and snowball sampling of midwives, doctors, social workers and link workers, from community and hospital settings. Interviewed individually and in small focus groups. All interviews were semi-structured, taped, transcribed, coded and organised using NVivo software and analysed using an inductive, thematic analysis. Results: 80 women consented, 27 were interviewed. Greater diversity of women (age, parity, socioeconomic status, ethnicity) than stereotypical 'late bookers' reported elsewhere was found. Four key groups of women were identified with explanatory subthemes for late booking: (1) the 'not knowers' (absence of classic symptoms, misinterpreters, not believing pregnant); (2) the 'knowers – avoiders' (ambivalence, fear, DIY care); (3) the 'knowers – postponers' (fearful, on the move, undecided, not valuing antenatal care); (4) The 'knowers – delayees' (professional and system failures, knowledge and acceptance of the 'system'). 42 stakeholders consented to interview; 8 focus groups and 9 individual interviews. Key themes were: a stereotypical view of socio-cultural and educational status of late bookers; lack of pregnancy planning and knowledge; ambivalence towards pregnancy/antenatal care; socio-cultural influences (chaotic lives, substance misuse, immigration, housing); vulnerability and support (influence of family and peers); fear, denial and avoidance (concealment, relationships with professionals, expectations); practical and organisational barriers to timely care. Conclusion: In this largest UK qualitative study to date we identified service user and healthcare factors which delay access to antenatal care, including delayed diagnosis of pregnancy, poor reproductive health knowledge, contraceptive failure, lack of lay facilitation of engagement with antenatal care, and individual socio-cultural risk factors. These factors should be considered by service commissioners and health and social care practitioners in order to promote the provision of timely antenatal care for all women.